Postexercise hot-water immersion does not further enhance heat adaptation or performance in endurance athletes training in a hot environment - Stevens, C. J.; Ross, M. L.; Carr, A. J.; Vallance, B.; Best, R.; Urwin, C.; Périard, J. D.; Burke, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Hot-water immersion (HWI) after training in temperate conditions has been shown to induce thermophysiological adaptations and improve endurance performance in the heat; however, the potential additive effects of HWI and training in hot outdoor conditions remain unknown. Therefore, this study aimed to determine the effect of repeated postexercise HWI in athletes training in a hot environment. Methods: A total of 13 (9 female) elite/preelite racewalkers completed a 15-day training program in outdoor heat (mean afternoon high temperature = 34.6°C). Athletes were divided into 2 matched groups that completed either HWI (40°C for 30-40 min) or seated rest in 21°C (CON), following 8 training sessions. Pre-post testing included a 30-minute fixed-intensity walk in heat, laboratory incremental walk to exhaustion, and 10,000-m outdoor time trial. Results: Training frequency and volume were similar between groups (P = .54). Core temperature was significantly higher during immersion in HWI (38.5 [0.3]) than CON (37.8°C [0.2°C]; P < .001). There were no differences between groups in resting or exercise rectal temperature or heart rate, skin temperature, sweat rate, or the speed at lactate threshold 2, maximal O2 uptake, or 10,000-m performance (P > .05). There were significant (P < .05) pre-post differences for both groups in submaximal exercising heart rate (~11 beats/min), sweat rate (0.34-0.55 L/h) and thermal comfort (1.2-1.5 arbitrary units), and 10,000-m racewalking performance time (~3 min). Conclusions: Both groups demonstrated significant improvement in markers of heat adaptation and performance; however, the addition of HWI did not provide further enhancements. Improvements in adaptation appeared to be maximized by the training program in hot conditions.